Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

On the vertical variability of turbulent heat fluxes within and above a deciduous forest - Temple R. Lee; Sandip Pal; Praveena Krishnan; Tim B. Wilson; Rick D. Saylor; Tilden P. Meyers; John Kochendorfer; Will Pendergrass; Randy White; Mark Heuer (Agricultural and Forest Meteorology, 2025)

Recognising and Protecting the National Benefit of Sustainable Fisheries in the UK - Sarah Coulthard; Ainsley Hatt; Phoebe Lewis; Bryce D. Stewart; Michael Roach; Robert Clark; Sam Fanshawe; Carole Sandrine White; Julie Urquhart; Jerry Percy; Tim Gray; Emily Bulled; et al. (Fish and Fisheries, 2025)
Sustainable commercial fishing makes valuable contributions to coastal regions and broader national benefits. This paper offers three arguments in relation to what is required for the societal benefits of sustainable fisheries to be fully realised and considers each in the context of the UK but with global relevance. First, there is a need to raise the profile of the full range of benefits that are delivered through sustainable fisheries to coastal communities and the broader public. In the UK, the delivery of a ‘national benefit’ objective through fisheries is now enshrined in law by the Fisheries Act, 2020; we operationalise this through a new framing that distils eight ‘national benefits’ that all sustainable fisheries should deliver. Second, better acknowledgement of what society gains from sustainable fisheries must be paralleled with recognition of what society is simultaneously at risk of losing through the decline of the fishing fleet. We detail this decline in a new analysis of long‐term UK data, which highlights that the decline is unequally felt, with some regions of the UK, and small‐scale fishing sectors, experiencing loss more acutely. This reality leads us to argue a third point, that if society is to retain and truly harness the benefits that flow from sustainable fisheries, governing bodies must act quickly to ensure that fisheries are environmentally sustainable, diverse and inclusive, pursuing fisheries that ‘leave no one behind’.

On the application of the hockey-stick transition hypothesis to characterize turbulence within and above a deciduous forest - Temple R. Lee; Sandip Pal; Praveena Krishnan; Tim B. Wilson; Rick D. Saylor; Tilden P. Meyers; John Kochendorfer; Will Pendergrass; Randy White; Mark Heuer (Agricultural and Forest Meteorology, 2025)

Current state of plant conservation translocations across Europe: motivations, challenges and outcomes - Sandrine Godefroid; Sam Lacquaye; Andreas Ensslin; Sarah Dalrymple; Thomas Abeli; Hannah Branwood; Inmaculada Ferrando Pardo; P. Pablo Ferrer Gallego; Elke Zippel; Luísa Gouveia; Carlos Alberto Lobo; Francisco Fernandes; et al. (Biodiversity and Conservation, 2025)

The EGS Collab project: Outcomes and lessons learned from hydraulic fracture stimulations in crystalline rock at 1.25 and 1.5 km depth - Tim Kneafsey; Pat Dobson; Doug Blankenship; Paul Schwering; Mark White; Joseph P. Morris; Lianjie Huang; Tim Johnson; Jeff Burghardt; Earl Mattson; Ghanashyam Neupane; Chris Strickland; et al. (Geothermics, 2025)

Crystallinity and dissolution-recrystallization mechanism controlled As(V) retention by calcium phosphate - Yao Yan; Xun Cao; Jun Li; Hanxiao Zhang; Yongqiang Yang; Fanrong Chen; Runliang Zhu; Dong Liu; Tim White; Shijun Wu (Journal of Hazardous Materials, 2025)

Structured decision-making shows broad support from diverse stakeholders for habitat conservation and restoration in Kenya’s Central Highlands - Gwili E.M. Gibbon; Martin Dallimer; Hassan Golo; Humphrey Munene; Charlene A. Wandera; Monda N. Edson; Jane C. Gachura; Tim Hobbs; Festus Ihwagi; Stephen R. Ikhamati; Samson K. Ikiara; David Kimathi; et al. (Land Use Policy, 2024)

Age, origin and tectonic controls on rapid recent exhumation of the Sibela Mountains, Bacan, Indonesia - Juliane Hennig-Breitfeld; Robert Hall; Lloyd T. White; H. Tim Breitfeld; Marnie A. Forster; Richard A. Armstrong; Barry P. Kohn (International Journal of Earth Sciences, 2024)
The Sibela Mountains of the island of Bacan in eastern Indonesia contain one of the Earth’s youngest metamorphic complexes that is now exposed at elevations up to 2000 m. New mica 40 Ar/ 39 Ar and apatite (U–Th–Sm)/He data from metamorphic and igneous rocks indicate that these rocks were rapidly exhumed in the Pleistocene (c. 0.7 Ma). Exhumation of the metamorphosed Permo-Triassic basement (c. 249–257 Ma) was accompanied by metamorphism (recorded by schists) as well as partial melting (recorded by c. 1.4 Ma granitic dykes). These processes must have occurred at extremely high cooling and exhumation rates. The rapid exhumation on land was associated with significant subsidence in adjacent basins offshore that reach depths up to 2.4 km. Neogene metamorphic core complexes and other metamorphic complexes are well-known from eastern Indonesia, but they usually record much higher exhumation rates than those reported from older classic metamorphic core complexes found in other parts of the world and require a different formation mechanism. Unlike classic metamorphic core complexes that are characterized by low-angle detachment faults, the Bacan metamorphic rocks were exhumed on steep bounding normal faults forming a rectilinear block pattern. We suggest such complexes are termed metamorphic block complexes (MBC). The Bacan MBC is exceptionally young and like the other east Indonesian complexes was rapidly exhumed during subduction rollback. A flexure formed during arc-arc collision as the Sangihe forearc loaded the Halmahera forearc which reactivated steeply-dipping faults in a rectilinear chocolate block pattern. Graphical abstract

Using in-situ strain measurements to evaluate the accuracy of stress estimation procedures from fracture injection/shut-in tests - Yves Guglielmi; Mark McClure; Jeffrey Burghardt; Joseph P. Morris; Thomas Doe; Pengcheng Fu; Hunter Knox; Vince Vermeul; Tim Kneafsey; J. Ajo-Franklin; T. Baumgartner; K. Beckers; et al. (International Journal of Rock Mechanics and Mining Sciences, 2023)

From worst-case to reality – Case studies illustrating tiered refinement of consumer exposure to cosmetic ingredients - Sarah Tozer; Camilla Alexander-White; Ripal Amin; Françoise Audebert; Catherine Barratt; John O'Brien; Tim Burke; Dagmar Bury; Hermine Dika Nguea; Myrto Dimopoulou; Sarah Farahmand; Sabrina Fritz; et al. (Regulatory Toxicology and Pharmacology, 2023)

Concern about the human health implications of marine biodiversity loss is higher among less educated and poorer citizens: Results from a 14-country study in Europe - Sophie M. C. Davison; Mathew P. White; Sabine Pahl; Tim Taylor; Angel Borja; Oonagh McMeel; Paula Kellett; Bethany R. Roberts; Lora E. Fleming (Frontiers in Marine Science, 2023)
Introduction Marine biodiversity loss has direct and indirect effects on human health and wellbeing. Recent European data suggest that the public is aware of this, identifying marine biodiversity protection as its top research priority in terms of oceans and human health, rated higher than issues such as plastic, chemical, and microbial pollution. Methods The current study aimed to better understand key sociodemographic and personality predictors of concern about marine biodiversity loss and the desire for more research into marine biodiversity protection, in an attempt to support communication efforts targeting specific sectors in society. Data were drawn from nationally representative samples of 14 European countries (n = 14,167). Results Results show greater concern about marine biodiversity loss and support for more research into marine biodiversity protection by older adults, females, and individuals: (i) without (vs. with) a university degree; (ii) with lower (vs. middle) incomes; (iii) who identified as politically left-wing; (iv) who visited the coast more often; and (v) those with more open, agreeable and conscientious personalities. Discussion These results suggest that, although concern and research support are generally high among European citizens, policy makers and communicators need to take into consideration individual-level variation.

Phase evolution and arsenic immobilization of arsenate-bearing amorphous calcium phosphate - Yao Yan; Yanan Fang; Vivek Verma; Jun Li; Yong Wang; Yongqiang Yang; Fanrong Chen; Runliang Zhu; Shijun Wu; Thomas J.N. Hooper; Tim White (Journal of Hazardous Materials, 2023)

Deep long period seismicity preceding and during the 2021 Fagradalsfjall eruption, Iceland - Tim Greenfield; Tom Winder; Nicholas Rawlinson; John Maclennan; Robert S. White; Thorbjörg Ágústsdóttir; Conor A. Bacon; Bryndís Brandsdóttir; Eva P. S. Eibl; Esme Glastonbury-Southern; Egill Árni Gudnason; Gylfi Páll Hersir; et al. (Bulletin of Volcanology, 2022)
We use a dense seismic network on the Reykjanes Peninsula, Iceland, to image a group of earthquakes at 10–12 km depth, 2 km north-east of 2021 Fagradalsfjall eruption site. These deep earthquakes have a lower frequency content compared to earthquakes located in the upper, brittle crust and are similar to deep long period (DLP) seismicity observed at other volcanoes in Iceland and around the world. We observed several swarms of DLP earthquakes between the start of the study period (June 2020) and the initiation of the 3-week-long dyke intrusion that preceded the eruption in March 2021. During the eruption, DLP earthquake swarms returned 1 km SW of their original location during periods when the discharge rate or fountaining style of the eruption changed. The DLP seismicity is therefore likely to be linked to the magma plumbing system beneath Fagradalsfjall. However, the DLP seismicity occurred ~ 5 km shallower than where petrological modelling places the near-Moho magma storage region in which the Fagradalsfjall lava was stored. We suggest that the DLP seismicity was triggered by the exsolution of CO 2 -rich fluids or the movement of magma at a barrier to the transport of melt in the lower crust. Increased flux through the magma plumbing system during the eruption likely adds to the complexity of the melt migration process, thus causing further DLP seismicity, despite a contemporaneous magma channel to the surface.

Long-Term Drought and Warming Alter Soil Bacterial and Fungal Communities in an Upland Heathland - Fiona M. Seaton; Sabine Reinsch; Tim Goodall; Nicola White; Davey L. Jones; Robert I. Griffiths; Simon Creer; Andy Smith; Bridget A. Emmett; David A. Robinson (Ecosystems, 2022)
The response of soil microbial communities to a changing climate will impact global biogeochemical cycles, potentially leading to positive and negative feedbacks. However, our understanding of how soil microbial communities respond to climate change and the implications of these changes for future soil function is limited. Here, we assess the response of soil bacterial and fungal communities to long-term experimental climate change in a heathland organo-mineral soil. We analysed microbial communities using Illumina sequencing of the 16S rRNA gene and ITS2 region at two depths, from plots undergoing 4 and 18 years of in situ summer drought or warming. We also assessed the colonisation of Calluna vulgaris roots by ericoid and dark septate endophytic (DSE) fungi using microscopy after 16 years of climate treatment. We found significant changes in both the bacterial and fungal communities in response to drought and warming, likely mediated by changes in soil pH and electrical conductivity. Changes in the microbial communities were more pronounced after a longer period of climate manipulation. Additionally, the subsoil communities of the long-term warmed plots became similar to the topsoil. Ericoid mycorrhizal colonisation decreased with depth while DSEs increased; however, these trends with depth were removed by warming. We largely ascribe the observed changes in microbial communities to shifts in plant cover and subsequent feedback on soil physicochemical properties, especially pH. Our results demonstrate the importance of considering changes in soil microbial responses to climate change across different soil depths and after extended periods of time.

Further description of the Kerguelen sandpaper skate Bathyraja irrasa (Rajiformes: Arhynchobatidae) based on additional specimens, including egg cases and embryos - William T. White; Helen L. O'Neill; Jaimie Cleeland; Tim D. Lamb (Journal of Fish Biology, 2022)
Adult specimens, additional juvenile specimens, egg cases and embryos were used to provide a more detailed anatomical description of the Kerguelen sandpaper skate Bathyraja irrasa , a species of skate endemic to the Kerguelen Plateau and listed as Vulnerable by the IUCN Red List of Threatened Species. The morphological and meristic data reveal a relatively high level of intraspecific variation, mostly related to size. Egg cases are described for the first time and were shown to vary in colour and fouling depending on the length of time spent in the marine environment. Embryos removed from egg cases represent all stages of embryonic development in this species and include the largest embryo recorded for this species, i.e. , 230 mm total length ( L T ), which increases the range of size at hatching of B. irrasa to 178–230 mm L T . A number of morphometric and meristic characters varied ontogenetically in B. irrasa , in particular relative tail length, number of tail thorns in the median row and the size of orbits. This study highlights the importance of describing intraspecific variation in species and the importance of egg cases to taxonomic and biological research on oviparous species.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

The health and well-being effects of drought: assessing multi-stakeholder perspectives through narratives from the UK - Kimberly Bryan; Sarah Ward; Liz Roberts; Mathew P. White; Owen Landeg; Tim Taylor; Lindsey McEwen (Climatic Change, 2020)
The global literature on drought and health highlights a variety of health effects for people in developing countries where certain prevailing social, economic and environmental conditions increase their vulnerability especially with climate change. Despite increased focus on climate change, relatively less is known about the health-drought impacts in the developed country context. In the UK, where climate change–related risk of water shortages has been identified as a key area for action, there is need for better understanding of drought-health linkages. This paper assesses people’s narratives of drought on health and well-being in the UK using a source-receptor-impact framing. Stakeholder narratives indicate that drought can present perceived health and well-being effects through reduced water quantity, water quality, compromised hygiene and sanitation, food security, and air quality. Heatwave associated with drought was also identified as a source of health effects through heat and wildfire, and drought-related vectors. Drought was viewed as potentially attributing both negative and positive effects for physical and mental health, with emphasis on mental health. Health impacts were often complex and cross-sectoral in nature indicating the need for a management approach across several sectors that targets drought and health in risk assessment and adaptation planning processes. Two recurring themes in the UK narratives were the health consequences of drought for ‘at-risk’ groups and the need to target them, and that drought in a changing climate presented potential health implications for at-risk groups.

Data rescue in manuscripts: a hydrological modelling study example - Xuan Yu; Anna Lamačová; Lele Shu; Christopher Duffy; Pavel Krám; Jakub Hruška; Tim White; Kairong Lin (Hydrological Sciences Journal, 2020)

Komodo dragons are not ecological analogs of apex mammalian predators - Tim S. Jessop; Achmad Ariefiandy; David M. Forsyth; Deni Purwandana; Craig R. White; Yunias Jackson Benu; Thomas Madsen; Henry J. Harlow; Mike Letnic (Ecology, 2020)
Apex predators can have substantial and complex ecological roles in ecosystems. However, differences in species‐specific traits, population densities, and interspecific interactions are likely to determine the strength of apex predators’ roles. Here we report complementary studies examining how interactions between predator per capita metabolic rate and population density influenced the biomass, population energy use, and ecological effects of apex predators on their large mammalian prey. We first investigated how large mammal prey resources and field metabolic rates of terrestrial apex predators, comprising large mammals and the Komodo dragon ( Varanus komodoensis ), influenced their biomass densities and population energy use requirements. We next evaluated whether Komodo dragons, like apex mammalian predators, exerted top‐down regulation of their large mammal prey. Comparison of results from field studies demonstrates that Komodo dragons attain mean population biomass densities that are 5.75−231.82 times higher than that of apex mammalian predator species and their guilds in Africa, Asia, and North America. The high biomass of Komodo dragons resulted in 1.96−108.12 times greater population energy use than that of apex mammalian predators. Nevertheless, substantial temporal and spatial variation in Komodo dragon population energy use did not regulate the population growth rates of either of two large mammal prey species, rusa deer ( Rusa timorensis ) and wild pig ( Sus scrofa ). We suggest that multiple processes weaken the capacity of Komodo dragons to regulate large mammal prey populations. For example, a low per capita metabolic rate requiring an infrequent and inactive hunting strategy (including scavenging), would minimize lethal and nonlethal impacts on prey populations. We conclude that Komodo dragons differ in their predatory role from, including not being the ecological analogs of, apex mammalian predators.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Current and projected global distribution of Phytophthora cinnamomi , one of the world's worst plant pathogens - Treena I. Burgess; John K. Scott; Keith L. Mcdougall; Michael J. C. Stukely; Colin Crane; William A. Dunstan; Frances Brigg; Vera Andjic; Diane White; Tim Rudman; Frans Arentz; Noboru Ota; et al. (Global Change Biology, 2017)
Globally, Phytophthora cinnamomi is listed as one of the 100 worst invasive alien species and active management is required to reduce impact and prevent spread in both horticulture and natural ecosystems. Conversely, there are regions thought to be suitable for the pathogen where no disease is observed. We developed a climex model for the global distribution of P. cinnamomi based on the pathogen's response to temperature and moisture and by incorporating extensive empirical evidence on the presence and absence of the pathogen. The climex model captured areas of climatic suitability where P. cinnamomi occurs that is congruent with all available records. The model was validated by the collection of soil samples from asymptomatic vegetation in areas projected to be suitable by the model for which there were few records. DNA was extracted, and the presence or absence of P. cinnamomi was determined by high‐throughput sequencing ( HTS ). While not detected using traditional isolation methods, HTS detected P. cinnamomi at higher elevations in eastern Australia and central Tasmania as projected by the climex model. Further support for the climex model was obtained using the large data set from south‐west Australia where the proportion of positive records in an area is related to the Ecoclimatic Index value for the same area. We provide for the first time a comprehensive global map of the current P. cinnamomi distribution, an improved climex model of the distribution, and a projection to 2080 of the distribution with predicted climate change. This information provides the basis for more detailed regional‐scale modelling and supports risk assessment for governments to plan management of this important soil‐borne plant pathogen.

Modelling long-term water yield effects of forest management in a Norway spruce forest - Xuan Yu; Anna Lamačová; Christopher Duffy; Pavel Krám; Jakub Hruška; Tim White; Gopal Bhatt (Hydrological Sciences Journal, 2015)

A synthesis of methane emissions from 71 northern, temperate, and subtropical wetlands - Merritt R. Turetsky; Agnieszka Kotowska; Jill Bubier; Nancy B. Dise; Patrick Crill; Ed R. C. Hornibrook; Kari Minkkinen; Tim R. Moore; Isla H. Myers‐Smith; Hannu Nykänen; David Olefeldt; Janne Rinne; et al. (Global Change Biology, 2014)
Wetlands are the largest natural source of atmospheric methane. Here, we assess controls on methane flux using a database of approximately 19 000 instantaneous measurements from 71 wetland sites located across subtropical, temperate, and northern high latitude regions. Our analyses confirm general controls on wetland methane emissions from soil temperature, water table, and vegetation, but also show that these relationships are modified depending on wetland type (bog, fen, or swamp), region (subarctic to temperate), and disturbance. Fen methane flux was more sensitive to vegetation and less sensitive to temperature than bog or swamp fluxes. The optimal water table for methane flux was consistently below the peat surface in bogs, close to the peat surface in poor fens, and above the peat surface in rich fens. However, the largest flux in bogs occurred when dry 30‐day averaged antecedent conditions were followed by wet conditions, while in fens and swamps, the largest flux occurred when both 30‐day averaged antecedent and current conditions were wet. Drained wetlands exhibited distinct characteristics, e.g. the absence of large flux following wet and warm conditions, suggesting that the same functional relationships between methane flux and environmental conditions cannot be used across pristine and disturbed wetlands. Together, our results suggest that water table and temperature are dominant controls on methane flux in pristine bogs and swamps, while other processes, such as vascular transport in pristine fens, have the potential to partially override the effect of these controls in other wetland types. Because wetland types vary in methane emissions and have distinct controls, these ecosystems need to be considered separately to yield reliable estimates of global wetland methane release.

Breeding for value in a changing world: past achievements and future prospects - Tim White; John Davis; Salvador Gezan; Jiri Hulcr; Eric Jokela; Matias Kirst; Timothy A. Martin; Gary Peter; Greg Powell; Jason Smith (New Forests, 2014)

SoilTrEC: a global initiative on critical zone research and integration - Manoj Menon; Svetla Rousseva; Nikolaos P. Nikolaidis; Pauline van Gaans; Panos Panagos; Danielle Maia de Souza; Kristin Vala Ragnarsdottir; Georg J. Lair; Liping Weng; Jaap Bloem; Pavel Kram; Martin Novak; et al. (Environmental Science and Pollution Research, 2014)

Crops that feed the world 9. Oats- a cereal crop for human and livestock feed with industrial applications - Athole Marshall; Sandy Cowan; Simon Edwards; Irene Griffiths; Catherine Howarth; Tim Langdon; Ethel White (Food Security, 2013)

A reassessment of late glacial – Holocene diatom oxygen isotope record from Lake Baikal using a geochemical mass‐balance approach - Anson W. Mackay; George E. A. Swann; Tim S. Brewer; Melanie J. Leng; David W. Morley; Natalia Piotrowska; Patrick Rioual; Dustin White (Journal of Quaternary Science, 2011)
We present a new palaeoenvironmental record of hydrological variability in Lake Baikal, based on re‐modelled δ 18 O diatom values of diatom silica (δ 18 O modelled ), where the residual contaminants are identified and compensated for using electron optical imaging and whole‐sample geochemistry. δ 18 O modelled interpretations are based on the balance between rivers with high δ 18 O values and rivers with low δ 18 O values. Isotopic variability is related to latitudinal differences in precipitation which feed these rivers. The δ 18 O modelled record suggests that rather moist conditions prevailed in the Lake Baikal region during the latter stages of the Younger Dryas. Throughout the Holocene, episodes of low δ 18 O modelled values are, in general, in good agreement with increases in percentage haematite‐stained grains in North Atlantic sediments (indicative of ice‐rafted debris events). Rivers with southerly catchments dominate fluvial input especially between c . 3.3 and 2 cal ka BP, concurrent with high precipitation in the Lake Baikal region. Copyright © 2011 John Wiley & Sons, Ltd.

Treatment of drainage from acidic canelands using a constructed wetland - Robert Quirk; Mike Melville; Andrew Kinsela; Jason Reynolds; Tim Zwemer; Marty Hancock; Ben Macdonald; Ian White (Sugar Tech, 2009)

Functional MRI of Language in Aphasia: A Review of the Literature and the Methodological Challenges - Bruce Crosson; Keith McGregor; Kaundinya S. Gopinath; Tim W. Conway; Michelle Benjamin; Yu-Ling Chang; Anna Bacon Moore; Anastasia M. Raymer; Richard W. Briggs; Megan G. Sherod; Christina E. Wierenga; Keith D. White (Neuropsychology Review, 2007)

The dynamic structure underlying subthreshold oscillatory activity and the onset of spikes in a model of medial entorhinal cortex stellate cells - Horacio G. Rotstein; Tim Oppermann; John A. White; Nancy Kopell (Journal of Computational Neuroscience, 2006)

Chirp sub-bottom profiler source signature design and field testing - Martin Gutowski; Jon Bull; Tim Henstock; Justin Dix; Peter Hogarth; Tim Leighton; Paul White (Marine Geophysical Research, 2002)